BUSINESS GAMES IN QUASI-PROFESSIONAL FUTURE TEACHERS’ TRAINING TO THE DEVELOPMENT OF GIFTED CHILDREN - Demchenko Оlena; Kit, Galina; Holiuk, Oksana; Rodiuk, Nataliia; Pakhalchuk, Natalia; Hryhorovych, Olha (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The relevance of the selection and development of the independent component of the preparing the future specialists of psychological and pedagogical profile in a higher educational institution, the purpose of which is to develop students’ competence in developing children’s giftedness, is substantiated. The arguments according to the need of the development of requirements and complex of qualities and skills for identifying and developing of children’s giftedness by the future teachers, starting with teachers of preschool education institutions, are given. The complexity and inconsistency of the forming the gifted individuals, the presence of special educational needs due to high abilities, original thinking, special worldview, asynchrony and other manifestations of giftedness are shown. The results of a students’ questioning regarding the using the business games in the process of preparing them for working with gifted children are presented. The significance of quasi-professional activity in general and business games in particular during the preparing the future teachers for the development of children’s giftedness is revealed. On the basis of the generalization of working experience, the pedagogical conditions of its successful organization in teaching the basic disciplines are highlighted.